Deciphering the mechanism of PSORI-CM02 in suppressing keratinocyte proliferation through the mTOR/HK2/glycolysis axis - Wang, Maojie; Tang, Bin; Huang, Huanjie; Wu, Xiaodong; Deng, Hao; Chen, Haiming; Mei, Liyan; Chen, Xiumin; Burgering, Boudewijn; Lu, Chuanjian (Frontiers in Pharmacology, 2023)
Hyperplasia of epidermal keratinocytes that depend on glycolysis is a new hallmark of psoriasis pathogenesis. Our previous studies demonstrated that PSORI-CM02 could halt the pathological progression of psoriasis by targeting inflammatory response and angiogenesis, but its effect(s) and mechanism(s) on proliferating keratinocytes remained unclear. In this study, we aim to identify components of PSORI-CM02 that are absorbed into the blood and to determine the effect(s) of PSORI-CM02 on keratinocyte proliferation and its molecular mechanism(s). We used the immortalized human epidermal keratinocyte cell line, HaCaT, as an in vitro model of proliferating keratinocytes and the imiquimod-induced psoriasis mouse (IMQ) as an in vivo model. Metabolite profiles of vehicle pharmaceutic serum (VPS), PSORI-CM02 pharmaceutic serum (PPS), and water extraction (PWE) were compared, and 23 components of PSORI-CM02 were identified that were absorbed into the blood of mice. Both PPS and PWE inhibited the proliferation of HaCaT cells and consequently reduced the expression of the proliferation marker ki67. Additionally, PPS and PWE reduced phosphorylation levels of mTOR pathway kinases. Seahorse experiments demonstrated that PPS significantly inhibited glycolysis, glycolytic capacity, and mitochondrial respiration, thus reducing ATP production in HaCaT cells. Upon treatments of PPS or PWE, hexokinase 2 (HK2) expression was significantly decreased, as observed from the set of glycolytic genes we screened. Finally, in the IMQ model, we observed that treatment with PSORI-CM02 or BPTES, an inhibitor of mTOR signaling, reduced hyperproliferation of epidermal keratinocytes, inhibited the expression of p-S6 and reduced the number of proliferating cell nuclear antigen (PCNA)-positive cells in lesioned skin. Taken together, we demonstrate that PSORI-CM02 has an anti-proliferative effect on psoriatic keratinocytes, at least in part, by inhibiting the mTOR/HK2/glycolysis axis.